1994
DOI: 10.1111/j.1365-2788.1994.tb00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Is clumsiness a marker for Asperger syndrome?

Abstract: ABSTRACT. Although Asperger syndrome (AS) has been included in the ICD‐10 as a distinct category within the pervasive developmental disorders, it is still unclear to what extent it differs from normal‐intelligence autism (high‐functioning autism; HFA). Persons with AS are said to be particularly clumsy. To test the hypothesis that clumsiness can reliably distinguish AS from autism, the present authors compared 11 patients with AS (ICD‐10; 10 males; mean age, 13–6 years; mean IQ, 98) with nine patients with HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(65 citation statements)
references
References 24 publications
5
59
0
Order By: Relevance
“…In each study children with ASD had significantly poorer motor abilities and more frequent subtle neurological signs compared to the control group. Studies have revealed that the rate of motor impairments generally converge on 80-90 percent of the cases [4][5][6][7][8][9]. Some of such studies confirmed this claim by comparing the scores of Peabody test and Bayley test in children with autism and their typical peers.…”
Section: Introductionsupporting
confidence: 52%
“…In each study children with ASD had significantly poorer motor abilities and more frequent subtle neurological signs compared to the control group. Studies have revealed that the rate of motor impairments generally converge on 80-90 percent of the cases [4][5][6][7][8][9]. Some of such studies confirmed this claim by comparing the scores of Peabody test and Bayley test in children with autism and their typical peers.…”
Section: Introductionsupporting
confidence: 52%
“…Motor difficulties in AS have been widely reported with some studies indicating the prevalence of such difficulties as exceeding 80% (Ghaziuddin, Tsai & Ghaziuddin, 1994;Miyahara et al, 1997). Difficulties with specific aspects of motor function have been reported as well as general clumsiness associated with poor motor planning, coordination and fine motor difficulties (Attwood;Green et al, 2003).…”
Section: Motor Function In Asperger's Syndromementioning
confidence: 99%
“…7 Other studies, however, have found no difference between autism and Asperger disorder on standardized motor assessments 8 and tests of coordination. 9 Thus, although there may be behavioural differences in motor function, this area is controversial.…”
mentioning
confidence: 99%